Experimental investigation and calculation of the binary (AgNO3 + KNO3) phase diagram. (February 2015) - Boa, D.; Hellali, D.; Licbarski, D.; Tizzotti, M.; Zamali, H.; Favotto, C.; Benigni, P.; Rogez, J.
Graphical abstract: Highlights: The existence of the solid compound AgK(NO3 )2 is ascertained. The melting of the AgK(NO3 )2 compound is non congruent. The AgK(NO3 )2 compound presents a (solid + solid) phase transition at T  = 408.7 K. Calculated (AgNO3  + KNO3 ) phase diagram is compared with our experimental data in the T  = 380–500 K range. Abstract: The (AgNO3  + KNO3 ) phase diagram is reinvestigated using differential thermal analysis and X-ray diffraction. The system is characterized by a non-congruent equimolar compound AgK(NO3 )2 with a polymorphic transition at T  = 408.7 K. Three invariant reactions are distinguished: an eutectoid, an eutectic and a peritectic at T  = (405.8, 407.8 and 415.9) K  ±  2 K respectively. The pure nitrates AgNO3 and KNO3 exhibit (solid + solid) phase transitions at T  = (428.9 and 404.5 K respectively. There is a solid solution of KNO3 in β -AgNO3 . In contrast, AgNO3 shows no significant solubility in solid KNO3 . Combining our results with experimental data available in the literature, an optimization of the thermodynamic parameters in the binary system is performed. The calculated phase diagram and the thermodynamic functions agree well with the experimental data.